Triazole GHS-R1a antagonists JMV4208 and JMV3002 attenuate food intake, body weight, and adipose tissue mass in mice - Holubová, M; Nagelová, V; Lacinová, Z; Haluzík, M; Sýkora, D; Moulin, A; Blayo, A L; Fehrentz, J A; Martinez, J; Stofkova, A; Jurčovičová, J; Zelezná, B; et al. (Molecular and cellular endocrinology, 2014)
The only peripherally released orexigenic hormone, ghrelin, plays a key role in food intake and body weight regulation. Antagonizing the ghrelin receptor, GHS-R1a, represents a promising approach for anti-obesity therapy. In our study, two novel GHS-R1a antagonists JMV4208 and JMV3002, which are trisubstituted 1,2,4-triazoles, decreased food intake in fasted lean mice in a dose-dependent manner, with ED50 values of 5.25 and 2.05 mg/kg, respectively. Both compounds were stable in mouse blood, with half-lives of 90 min (JMV4208) and 60 min (JMV3002), and disappeared from the blood 8h after administration. Fourteen days of treatment with the ghrelin antagonists (20 mg/kg twice a day) decreased food intake, body weight and adipose tissue mass in mice with diet-induced obesity (DIO). These results are likely attributable to an impact on food intake reduction and an attenuated expression of the lipogenesis-promoting enzymes (acetyl-CoA carboxylase 1 in subcutaneous fat and fatty acid synthase in subcutaneous and intraperitoneal fat). The decrease in fat mass negatively impacted circulating leptin levels. These data suggest that JMV4208 and JMV3002 could be useful therapeutic agents for the treatment of obesity.
Keywords: Triazoles; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Picolinic Acids; receptory ghrelinu; myši inbrední C57BL; Mice; Eating; Body Weight; kyseliny pikolinové; zvířata; triazoly; tělesná hmotnost; Receptors, Ghrelin; Adipose Tissue; myši; tuková tkáň; Mice, Inbred C57BL; přijímání potravy; Animals